2019
DOI: 10.4274/jcrpe.galenos.2018.2018.0162
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Premature Small for Gestational Age Infants Have Appropriate Catch-up Growth at Term Equivalence Compared with Extreme Premature Appropriate for Gestational Age Infants

Abstract: Recent studies have shown that small for gestational age (SGA) term infants undergo catch-up growth during infancy but there is limited studies on early growth outcomes of extreme premature SGA infants. The aim of this study was to compare factors associated during birth in extremely premature infants less than 28 weeks’ gestation who were born SGA (<10 th percentile for gestational age) with those who were born appropriate-for-gestational age (AGA) (10 th -89 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies reported that growth restriction was more common in preterm infants but recent studies have shown positive reports of catch-up growth through nutritional support and quality improvement [26]. Small for gestational age infants with less than 28 week's gestation had appropriate catch-up growth at term, improved with postnatal nutrition and care [27]. Early HC growth failure in very preterm infants can be improved by optimizing parenteral nutrition [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that growth restriction was more common in preterm infants but recent studies have shown positive reports of catch-up growth through nutritional support and quality improvement [26]. Small for gestational age infants with less than 28 week's gestation had appropriate catch-up growth at term, improved with postnatal nutrition and care [27]. Early HC growth failure in very preterm infants can be improved by optimizing parenteral nutrition [28].…”
Section: Discussionmentioning
confidence: 99%
“…This rapid gain in FM is similar to the classic pattern of ‘catch-up’ growth reported in premature and small-for-gestational age babies. 13 Nevertheless, it is not possible to be conclusive regarding the effects of FM catch-up without an in-depth analysis of FM accrual velocity. 14 Currently, prescriptive standards for FM and FFM accretion velocity do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal growth is divided into the infancy, childhood, and adolescent periods, and growth failure in any of these periods increases the possibility of short stature in adulthood. 22,23) Growth in early childhood, particularly during the 24 months after birth, has an impact on growth in later childhood and puberty, 24) ultimately leading to final adult height. In this study, 3 of 63 preterm AGA infants (4.8%) had growth failure at 24 months.…”
Section: Discussionmentioning
confidence: 99%